EXPLORING THE CONTRIBUTION OF VIDEO GAMES TO ENGLISH VOCABULARY ACQUISITION AND RETENTION ACROSS VARIOUS GAME GENRES - Jessica Natalyn Santoso Hadi; Alberik Ryan Tendy Wijaya (Magister Scientiae, 2025)
Vocabulary is essential for language learners, particularly those studying English. Beyond formal institutions and structured settings, vocabulary can also be learned and acquired through video games. Incidental learning plays a significant role in this process, as it helps students retain and recall various words. Mastery of vocabulary also depends on students' preferences for video game genres, as these preferences influence their ability to retain vocabulary for longer periods through engaging and unique experiences. Each video game genre offers varying levels of vocabulary difficulty and frequency, contributing differently to the learning process. This study explores students' perceptions of using video games to enhance their English vocabulary. A descriptive research approach was employed to investigate the preferences of eleventh-grade students from a private high school. Data were collected through questionnaires and interviews. The findings reveal a positive correlation between video game engagement and improved vocabulary retention across various game genres. The majority of students highlighted those video games which featuring rich narrative interactions were particularly effective in helping them recall vocabulary more easily.